You are on page 1of 6

# 𝒚 = √𝒙

𝒚𝟐 = 𝒙
(𝒚 + 𝜹𝒚)𝟐 = 𝒙 + 𝜹𝒙
𝒚𝟐 + 𝟐𝒙𝜹𝒚 + (𝜹𝒚)𝟐 = 𝒙 + 𝜹𝒙
𝒚𝟐 + 𝟐𝒚𝜹𝒚 + (𝜹𝒚)𝟐 − 𝒚𝟐 = 𝒙 + 𝜹𝒙 − 𝒙
𝟐𝒚𝜹𝒚 + (𝜹𝒚)𝟐 = 𝜹𝒙
𝟐𝒚𝜹𝒚 + (𝜹𝒚)𝟐 𝜹𝒙
=
𝜹𝒙𝜹𝒚 𝜹𝒙𝜹𝒚
𝟏 𝟏
(𝟐𝒚 + 𝜹𝒚) =
𝜹𝒙 𝜹𝒚
𝜹𝒚
(𝟐𝒚 + 𝜹𝒚) = 𝟏
𝜹𝒙
𝜹𝒚
𝐥𝐢𝐦 ∙ 𝐥𝐢𝐦 (𝟐𝒚 + 𝜹𝒚) = 𝐥𝐢𝐦 𝟏
𝜹𝒙→𝟎 𝜹𝒙 𝜹𝒚→𝟎 𝜹𝒙→𝟎

𝒅𝒚
∙ 𝟐𝒚 = 𝟏
𝒅𝒙
𝒅𝒚 𝟏
=
𝒅𝒙 𝟐𝒚
𝒅𝒚 𝟏
=
𝒅𝒙 𝟐√𝒙

𝟏
𝒚 = (𝒙𝟐 + 𝟏)𝟒
𝒚𝟒 = 𝒙𝟐 + 𝟏
(𝒚 + 𝜹𝒚)𝟒 = (𝒙 + 𝜹𝒙)𝟐 + 𝟏
(𝒚 + 𝜹𝒚)𝟒 − 𝒚𝟒 = (𝒙 + 𝜹𝒙)𝟐 + 𝟏 − (𝒙𝟐 + 𝟏)
𝒚𝟒 + 𝟒𝒚𝟑 𝜹𝒚 + 𝟔𝒚𝟐 (𝜹𝒚)𝟐 + 𝟒𝒚(𝜹𝒚)𝟑 + (𝜹𝒚)𝟒 − 𝒚𝟒
= 𝒙𝟐 + 𝟐𝒙(𝜹𝒙) + (𝜹𝒙)𝟐 + 𝟏 − (𝒙𝟐 + 𝟏)
𝟒𝒚𝟑 𝜹𝒚 + 𝟔𝒚𝟐 (𝜹𝒚)𝟐 + 𝟒𝒚(𝜹𝒚)𝟑 + (𝜹𝒚)𝟒 = 𝟐𝒙𝜹𝒙 + (𝜹𝒙)𝟐
𝟒𝒚𝟑 𝜹𝒚 + 𝟔𝒚𝟐 (𝜹𝒚)𝟐 + 𝟒𝒚(𝜹𝒚)𝟑 + (𝜹𝒚)𝟒 𝟐𝒙𝜹𝒙 + (𝜹𝒙)𝟐
=
𝜹𝒙 𝜹𝒙
𝟒𝒚𝟑 + 𝟔𝒚𝟐 𝜹𝒚 + 𝟒𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 𝟐𝒙 + 𝜹𝒙
=
𝜹𝒙 𝜹𝒚
𝜹𝒚
(𝟒𝒚𝟑 + 𝟔𝒚𝟐 𝜹𝒚 + 𝟒𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 ) = 𝟐𝒙 + 𝜹𝒙
𝜹𝒙
𝜹𝒚
𝐥𝐢𝐦 ∙ 𝐥𝐢𝐦 [𝟒𝒚𝟑 + 𝟔𝒚𝟐 𝜹𝒚 + 𝟒𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 ] = 𝐥𝐢𝐦 (𝟐𝒙 + 𝜹𝒙)
𝜹𝒙→𝟎 𝜹𝒙 𝜹𝒚→𝟎 𝜹𝒙→𝟎

𝒅𝒚 𝒅𝒚 𝟐𝒙
𝟒𝒚𝟑 = 𝟐𝒙 → = 𝟑
𝒅𝒙 𝒅𝒙 𝟒𝒚
𝒅𝒚 𝟐𝒙 𝟐𝒙
= =
𝒅𝒙 𝟏 𝟑 𝟑
(𝟒(𝒙𝟐 + 𝟏)𝟒 ) 𝟒(𝒙𝟐 + 𝟏)𝟒

1
𝑦 = (𝑥 + 2)6
1
1 3
𝑦 = ((𝑥 + 2)2 )
1
𝑦 3 = (𝑥 + 2)2
𝟏
(𝑦 + 𝜹𝒚)𝟑 = (𝑥 + 𝜹𝒙 + 𝟐)𝟐
𝟏
𝑦 3 + 3𝑦 2 𝜹𝒚 + 𝟑𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 = (𝒙 + 𝜹𝒙 + 𝟐)𝟐
𝟏 𝟏
𝑦 3 + 3𝑦 2 𝜹𝒚 + 𝟑𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 − 𝒚𝟑 = (𝒙 + 𝜹𝒙 + 𝟐)𝟐 − (𝒙 + 𝟐)𝟐

(𝒙 + 𝜹𝒙 + 𝟐) − (𝒙 + 𝟐)
3𝑦 2 𝜹𝒚 + 𝟑𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 = 𝟏 𝟏
(𝒙 + 𝜹𝒙 + 𝟐)𝟐 + (𝒙 + 𝟐)𝟐
𝜹𝒙
3𝑦 2 𝜹𝒚 + 𝟑𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 = 𝟏 𝟏
(𝒙 + 𝜹𝒙 + 𝟐)𝟐 + (𝒙 + 𝟐)𝟐

3𝑦 2 𝜹𝒚 + 𝟑𝒚(𝜹𝒚)𝟐 + (𝜹𝒚)𝟑 𝜹𝒙
= 𝟏 𝟏
𝜹𝒚 𝜹𝒙
𝜹𝒚 𝜹𝒙 [(𝒙 + 𝜹𝒙 + 𝟐)𝟐 + (𝒙 + 𝟐)𝟐 ]

3𝑦 2 + 3𝑦𝜹𝒚 + (𝜹𝒚)𝟐 𝟏
= 𝟏 𝟏
𝜹𝒙
𝜹𝒚 [(𝒙 + 𝜹𝒙 + 𝟐)𝟐 + (𝒙 + 𝟐)𝟐 ]

𝛿𝑦 1
[3𝑦 2 + 3𝑦𝛿𝑦 + (𝛿𝑦)2 ] = 𝟏 𝟏
𝛿𝑥
(𝒙 + 𝜹𝒙 + 𝟐)𝟐 + (𝒙 + 𝟐)𝟐
𝛿𝑦 1
lim lim [3𝑦 2 + 3𝑦𝛿𝑦 + (𝛿𝑦)2 ] = lim 1 1
𝛿𝑥→0 𝛿𝑥 𝛿𝑦→0 𝛿𝑥→0
(𝑥 + 𝛿𝑥 + 2)2 + (𝑥 + 2)2
𝑑𝑦 1 1 1
3𝑦 2 = 1 = 1 = 1
𝑑𝑥
2(𝑥 + 2)2 (3𝑦 2 )2(𝑥 + 2)2 6𝑦 2 (𝑥 + 2)2
𝑑𝑦 1 1 1
= 1 1 = 2 1 = 5
𝑑𝑥
6[(𝑥 + 2
2) ]6 (𝑥 + 2)2 6(𝑥 + 2)6+2 6(𝑥 + 2)6
𝑑𝑦 1 5
= (𝑥 + 2)−6
𝑑𝑥 6

1
= sec 𝐴 − tan 𝐴
sec 𝐴 + tan 𝐴
1 1 1 cos 𝐴
= = =
sec 𝐴 + tan 𝐴 1 sin 𝐴 1 − sin 𝐴 1 − sin 𝐴

cos 𝐴 cos 𝐴 cos 𝐴
cos 𝐴 (1 + sin 𝐴) cos 𝐴 (1 + sin 𝐴) cos 𝐴 (1 + sin 𝐴)
= = =
(1 − sin 𝐴)(1 + sin 𝐴) 1 − sin2 𝐴 cos 2 𝐴
1 + sin 𝐴 1 sin 𝐴
= = + = sec 𝐴 + tan 𝐴
cos 𝐴 cos 𝐴 cos 𝐴
1 sin 𝐴 1 − sin 𝐴 (1 − sin 𝐴)(1 + sin 𝐴)
sec 𝐴 − tan 𝐴 = − = =
cos 𝐴 cos 𝐴 cos 𝐴 cos 𝐴 (1 + sin 𝐴)

## 1 − sin2 𝐴 cos 2 𝐴 cos 𝐴

= = =
cos 𝐴 (1 + sin 𝐴) cos 𝐴 (1 + sin 𝐴) 1 + sin 𝐴
1 1 1 1
= = =
sec 𝐴 (1 + sin 𝐴) sec 𝐴 + sec 𝐴 sin 𝐴 sec 𝐴 + 1 sin 𝐴
cos 𝐴
1 1
= =
sin 𝐴 sec 𝐴 + tan 𝐴
secA +
cos 𝐴

Train A and B are at two different stations 100km apart. Train A took off at 10:30
am exactly and train B took off at 11:00 am with a speed of 10km/h faster than
train A. the two trains approached each other at a parallel track at exactly 1:00
pm. Find the speed and distance of each train at the time they met.

Solution

## Let 𝑥 𝑎𝑛𝑑 𝑦 be the distance covered by train A and Train B respectively.

At the time they met the sum of the distance covered by both trains is equal to
100km.

𝑥 + 𝑦 = 100 … (1)

## Train B is 10km/h faster than train A

Speed of train A

𝑥 𝑘𝑚
2.5 ℎ𝑜𝑢𝑟𝑠
At the time they met train A has used 10: 30𝑎𝑚 − 1: 00𝑝𝑚 =
2 ℎ𝑜𝑢𝑟𝑠 30 𝑚𝑖𝑛𝑢𝑡𝑒𝑠.

## And train B has used 11; 00𝑎𝑚 − 1: 00𝑝𝑚 = 2 ℎ𝑜𝑢𝑟𝑠

𝑦𝑘𝑚
Speed train B =
2 ℎ𝑜𝑢𝑟𝑠

𝑦𝑘𝑚 𝑥𝑘𝑚
But − 10𝑘𝑚ℎ−1 = … (2)
2 ℎ𝑜𝑢𝑟𝑠 2.5 ℎ𝑜𝑢𝑟𝑠

𝑦 2𝑥
− 10 =
2 5
5𝑦 − 100 = 4𝑥

5𝑦 − 100 = 4(100 − 𝑦)

5𝑦 + 4𝑦 = 500

5
𝑦 = 55 𝑘𝑚
9
5 4
𝑥 = 100 − 55 = 44 𝑘𝑚
9 9
400
800 7
Speed of Train A= 9
5 = = 17 𝑘𝑚ℎ−1
45 9
2

500
500 7
Speed of train B= 9
= = 27 𝑘𝑚ℎ−1
2 18 9

## Then B covered 100 – x at the time they met.

𝑥
Speed of A = kmh^-1
2.5

100 – 𝑥
Speed of B =
2

𝑥 100 − 𝑥
+ 10 =
2.5 2
2𝑥 + 50 = 250 − 2.5𝑥

4.5𝑥 = 200
200 4
𝑥= = 44 km
4.5 9